A conceptual framework for entrepreneurial orientation: is philanthropy missing in family business?. (23rd June 2020) - Gautam, Omvir; Agrawal, Pooja; Sharma, Dipti
The purpose of this study is to explore conceptual knowledge of entrepreneurial orientation by examining the moderating impact of family support. Theoretical model explains the importance and utility of an entrepreneurial orientation in the context of a family business. This study identifies ten dimensions in context to entrepreneurial orientation such as entrepreneur career, the transformation assimilation, entrepreneurial knowledge, innovation and idea generation, funds availability, entrepreneurial optimism, risk taking ability and recognising social and economic support by encompassing a moderating variable like family support. Based on the available literature from past studies in this paper, a conceptual framework has been constructed with ten major arguments (prepositions). This study significantly contributes in the form of a conceptual model of entrepreneurial orientation with philanthropic concern by entrepreneurs. Further, it explores the family support as an important moderator determinant to family business.